Innovative Control Approaches for Efficient Power Management in Hybrid Renewable Energy Resource Microgrids - Rubini B.; Bansal Saloni; Jadhav Dhiraj; Senthilkumar K.K.; Dhilipkumar R.; Pawar Avinash M.; Vivek V. (E3S Web of Conferences)
Hybrid renewable energy resource (RER) microgrids offer a sustainable solution to integrating multiple energy sources like solar and wind into modern power systems. However, managing the intermittent nature of these resources presents significant challenges in maintaining stable and efficient power distribution. This study explores innovative control approaches for optimizing power management in hybrid RER microgrids. By utilizing advanced algorithms, including real-time optimization and machine learning techniques, the proposed framework ensures efficient energy distribution, reduces dependency on the grid, and enhances system stability. The research focuses on integrating these control strategies to balance energy supply and demand while maximizing the utilization of renewable energy sources. Simulation results demonstrate the effectiveness of the proposed methods in improving system efficiency and reliability under varying environmental conditions, contributing to the broader adoption of hybrid RER microgrids.